Boosting optical nonlinearity in epsilon-near-zero trilayer coatings. Issue 16 (4th April 2023) - Guo, Zhida; Wu, Dong; Zhang, Feilian; Dong, Jiannan; Jiang, Xiaofang; Han, Peng; Chen, Yihang
Abstract : The ITO/Ag/ITO trilayer structure can significantly enhance the nonlinear response in the epsilon-near-zero region, which allows nonlinear optical devices to work at low power. Abstract : Materials with large optical nonlinearity are highly desired for various applications such as all-optical signal processing and storage. Recently, indium tin oxide (ITO) has been found to possess strong optical nonlinearity in the spectral region where its permittivity vanishes. Here, we demonstrate that ITO/Ag/ITO trilayer coatings, deposited by magnetron sputtering with high-temperature heat treatment, can significantly enhance the nonlinear response in their effective epsilon-near-zero (ENZ) regions. The obtained results show that the carrier concentrations of our trilayer samples can reach 7.25 × 10 21 cm −3, and the ENZ region can shift to the spectrum close to the visible range. In the ENZ spectral region, the ITO/Ag/ITO samples exhibit enhanced nonlinear refractive indices as large as 2.397 × 10 −15 m 2 W −1, over 27 times larger than that of an individual ITO layer. Such a nonlinear optical response is well described using a two-temperature model. Our findings provide a new paradigm for developing nonlinear optical devices for applications requiring low power.